Forms of Conversational Implicatures Between Sellers and Buyers at Kempas District Market - Eka Wati; Charlina; Oki Rasdana (Raja Zulkarnain Education Foundation, 2026)
This study aims to identify and analyze the forms of conversational implicatures used by sellers and buyers in buying and selling interactions at the Kempas District market. This study uses a descriptive qualitative method. The research data consists of sellers’ and buyers’ utterances containing conversational implicatures, with data sources coming from buying and selling interactions at Rumbai Jaya Market, Sungai Gantang Market, and Harapan Tani Market. Data collection techniques were carried out through observation, recording, and note-taking. Data analysis techniques used the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show three forms of conversational implicatures, namely 27 instances of general conversational implicatures, 21 instances of specific conversational implicatures, and 5 instances of scaled conversational implicatures. Of these three forms, general conversational implicatures are the most dominant form used in buying and selling interactions in the markets of Kempas District. This finding shows that the general conversational implicature form is predominantly found because most of the utterances in buying and selling transactions are conveyed directly, simply, and easily understood by the interlocutor without requiring additional context. These general implicatures give rise to many implied meanings, such as persuasive meanings, negotiation meanings, subtle sarcasm, and indirect rejection, which are used as strategies by both sellers and buyers in the bargaining process.